Synthesis and structural studies of dicationic Pd(II) and Pt(II) complexes of 2-(alkylchalcogenomethyl)pyridines, [MNC5H4-2-(CH2ER)2][PF6]2. (1st December 2018) - Jones, Roderick C.; Gardiner, Michael G.; Skelton, Brian W.; Tolhurst, Vicki-Anne
Graphical abstract: The synthesis and structural studies of novel dicationic platinum and palladium complexes containing heteroleptic pyridyl thioether/selenoether ligands of the formula [M(L)2 ][PF6 ]2 are described. Abstract: Six novel dicationic complexes of the formula [ML2 ][PF6 ]2, were prepared from the reaction of MCl2 (M = Pd, Pt) with two equivalents of Tl[PF6 ] in acetonitrile (MeCN), followed by addition of two equivalents of 2-(alkylchalcogenomethyl)pyridine ( N, E ) ligands (L) [L = 2-(methylthiomethyl)pyridine (L 1 ), 2-(phenylthiomethyl)pyridine (L 2 ), 2-(methylselenomethyl)pyridine (L 3 )] at room temperature. Structures of the synthesised complexes [M(L 1 )2 ][PF6 ]2 [M = Pd (1a ), Pt (1b )] and [M(L 3 )2 ][PF6 ]2 [M = Pd (3a ), Pt (3b )] were characterised by single crystal X-ray diffraction studies, illustrating they crystallise in the triclinic crystal system in the space group P 1 ¯ . The metal centres exhibit a distorted square planar geometry, with the donor atoms of the chelated N, E ligands arranged trans with respect to each other. The orientation of the methyl moieties of the ligands with respect to each other and the square planar metal were varied, with the methyl moieties in [Pt(L 3 )2 ][PF6 ]2 (3b ) having anti- geometry in the solid state while those of [M(L 1 )2 ][PF6 ]2 [M = Pd (1a ), Pt (1b )] and [Pd(L 3 )2 ][PF6 ]2 (3a ) show the methylselenoether groups to have syn -geometries with respect to themselves and the metal plane. All synthesised complexes were further characterised by elemental analysis, FT-IR spectroscopy and liquid secondary ionisation mass spectrometry (LSIMS) techniques.